Care pathway in sarcomas: klinična pot - Novak, Marko (Onkologija : Slovenian Journal of Oncology, 2019)
Abstract First treatment is crucial in the management of sarcoma patients, therefore it is essential to refer these patients to sarcoma centre. Diagnostic procedures and treatment have to proceed in sarcoma centre. First resection of the tumor has to be performed by a sarcoma surgeon. Institute of Oncology Ljubljana is the only referral centre for soft tissue sarcoma patients and Department of Orthopaedic surgery of the Ljubljana University Medical Centre is the only referral centre for bone sarcoma patients in Slovenia. In the absence of a diagnosis of malignant disease, rapidly growing and/or painfull tumors, all tumors deep to fascia and superficial tumors larger than 5 cm are suspicious for soft tissue sarcoma of the trunk and limbs; in retroperitoneum, tumors containing fat are suspicious for sarcoma. Patients with the tumor suspicious for soft tissue sarcoma or proven sarcoma schould be referred to the Institute of Oncology Ljubljana. Patients with the radiologic bone laesion suspicious for bone sarcoma schould be referred to the Department of Orthopaedic surgery of the Ljubljana University Medical Centre.